COMPARISON EFFECT OF CAUSTIC FUSION RATIO ON TIO2 ANATASE RESULTS AND EFFICIENCY IN DSSC APPLICATIONS: LITERATURE STUDY - Choir Fauzi, Fiqril
The development regarding the use of renewable energy continues to progress due to the increasing demand for energy over time. Utilization of solar energy for electricity can emerge as a solution. Dye-sensitized solar cell (DSSC) is an example of a device capable of doing this by utilizing a dye solution to excite electrons and generate electricity. Photoanode plays an important role in DSSC performance. The material commonly used as a photoanode is TiO2 because it is a semiconductor material that is non-toxic, easy to synthesis, stable and has abundant availability. This research will discuss about caustic fusion in ilmenite concentrate and its effect on DSSC efficiency. The study was carried out by collecting data from various sources to provide information on the synthesis of TiO2 and DSSC. The information is regarding the synthesis sequence from ilmenite concentrate to DSSC fabrication. In addition, data was collected regarding the effect of NaOH composition during caustic fusion on anatase TiO2 and its effect on DSSC efficiency and comparison of DSSC efficiency from various studies. All of this information is presented in form of table and graphic. Then, an analysis of the impact is carried out and the prospect for future research. The results of the literature study show that the differences in the composition of NaOH at the time of caustic fusion have an effect on the purity of anatase TiO2. Increasing the amount of NaOH tends to increase the purity of TiO2 and decrease the impurities in the extracted TiO2 powder such as Fe2O3. Then obtained the optimal parameters for caustic fusion such as 800o C temperature of caustic fusion, 1 hour time of caustic fusion and using NaOH as alkaline compound. Increasing the purity of TiO2 and decreasing Fe2O3 levels tends to increase the efficiency of the DSSC. Also obtained the optimal Fe2O3 content so that the optimal DSSC efficiency obtained is around 1%. When compared to the results of the DSSC efficiency from various studies, it is still found that the efficiency is lower than solar cells made from silicon so that research needs to be done again to increase the efficiency of the DSSC.